Redesigning ambulatory care management for uncontrolled type 2 diabetes: a prospective cohort study of the impact of a Boot Camp model on outcomes. Issue 1 (13th November 2019) - Magee, Michelle F; Baker, Kelley M; Fernandez, Stephen J; Huang, Chun-Chi; Mete, Mihriye; Montero, Alex R; Nassar, Carine M; Sack, Paul A; Smith, Kelly; Youssef, Gretchen A; Evans, Stephen R
Abstract : Objective: Type 2 diabetes care management (DCM) is challenging. Few studies report meaningful improvements in clinical care settings, warranting DCM redesign. We developed a Boot Camp to provide timely, patient-centered, technology-enabled DCM. Impact on hemoglobin A1c (HbA1c ), emergency department (ED) visits and hospitalizations among adults with uncontrolled type 2 diabetes were examined. Research design and methods: The intervention was designed using the Practical Robust Implementation and Sustainability Model to embed elements of the chronic care model. Adults with HbA1c > 9% (75 mmol/mol) enrolled between November 2014 and November 2017 received diabetes education and medication management by diabetes educators and nurse practitioners via initial clinic and subsequent weekly virtual visits, facilitated by near-real-time blood glucose transmission for 90 days. HbA1c and risk for ED visits and hospitalizations at 90 days, and potential savings from reducing avoidable medical utilizations were examined. Boot Camp completers were compared with concurrent, propensity-matched chart controls receiving usual DCM in primary care practices. Results: A cohort of 366 Boot Camp participants plus 366 controls was analyzed. Participants were 79% African-American, 63% female and 59% Medicare-insured or Medicaid-insured and mean age 56 years. Baseline mean HbA1c for cases and controls was 11.2% (99 mmol/mol) and 11.3% (100 mmol/mol), respectively. At 90 days, HbA1c was 8.1% (65 mmol/mol) and 9.9% (85 mmol/mol), p<0.001, respectively. Risk for 90-day all-cause hospitalizations decreased 77% for participants and increased 58% for controls, p=0.036. Mean potential for monetization of US$3086 annually per participant for averted hospitalizations were calculated. Conclusions: Redesigning diabetes care management using a pragmatic technology-enabled approach supported translation of evidence-based best practices across a mixed-payer regional healthcare system. Diabetes educators successfully participated in medication initiation and titration. Improvement in glycemic control, reduction in hospitalizations and potential for monetization was demonstrated in a high-risk cohort of adults with uncontrolled type 2 diabetes. Trial registration number: NCT02925312 .